The importance of international conferences on sustainable development as higher education institutions' strategies to promote sustainability: A case study in Brazil. (10th January 2018) - Berchin, Issa Ibrahim; Sima, Mihaela; de Lima, Maurício Andrade; Biesel, Shelly; dos Santos, Leandro Piazza; Ferreira, Renata Vilma; de Andrade Guerra, José Baltazar Salgueirinho Osório; Ceci, Flávio
Abstract: This paper analyzes the significance of international conferences for higher education institutions (HEIs)' promotion of sustainability. The paper has undertaken a detailed review of the scientific literature on strategies of HEIs to promote sustainability, hence identifying eight HEIs strategies that these institutions can adopt to become more sustainable (developing an Institutional Agenda, promoting Research, improving Teaching, enhancing green Campus Operations, stimulating community Outreach, and promoting Knowledge Dissemination). Based on this review, and focusing on knowledge dissemination, particularly on the academic events (conferences, seminars and workshops), 69 international academic conferences on sustainability were selected for analysis (from 2012 to 2016). From these conferences 21 proved suitable for a text mining analysis due to the data availability - i.e. articles published online. These articles were organized and submitted to the Collocations Extraction process, creating a list of important terms for each conference, based on their frequency in the articles. Furthermore, the relevance of these terms was tested using the Google Trends tool, to evidence the frequency of their Google searching. Finally, two conferences were selected for a more in-depth analysis, exploring their results and contributions (REGSA and LINKS conferences) to promote sustainability. The main results of the paper outline that international conferences have become important HEIs' strategies to promote various issues of sustainability, through sharing knowledge, experiences, projects, initiatives and methods. It can be noticed a high interdisciplinary and multidisciplinary character of these events, illustrated by the multitude of promoted topics and participation, but also an increasing interest to actively involve stakeholders in discussing and promoting sustainability and sustainable development. Highlights: International cooperation between HEIs plays a key role in promoting sustainable development. Collaboration among HEIs and multi-stakeholders' approaches create environment for practical learning for sustainability. International academic conferences promote inter/multi-disciplinary approaches to address global sustainability challenges.